The Eye and i of the incest offender the self-concept and the concept of the family of incest rape convicts at the New Bilibid Prison - Arca, Ashley Rein Coniely Angel A.; Leaño, Melanie M. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2019)
In the Philippines, familism is highly valued, however, in this country which gives prime to family-centeredness, cases of incest abuse are present. Incest, a deviant sexual behavior towards one's own relative, remains highly unreported compared to the actual number of incestuous abuse happening in reality, because of the culture of silence that surrounds it. This research aimed to counter the culture of silence to further prevail. This qualitative research is an exploratory study about the narratives of convicted incest rape offenders in the country. This research employed an interpretive approach through the narrative mode of inquiry, and specifically explored the familial interactions, describe the self-concept, descibed the perception on the deviant act, and discussed the concept of the family of four male, marrieed incest rape convict who shared their narratives through in-depth-semi-structured interviews. This research was guided by Structural Symbolic Interactionism (Stryker, 2002; Mead, 1934), Social Control Theory (Hirschi, 1969), and Guilt-Redemption Cyle (Burke, 1965). The researcher found various family of origin experiences of incest rape convicts before incarceration, showing that incest rape offenders come from different backgrounds. Three participants of the study had the same feeling of detachment with their wives before incarceration, while the other participant was left by his wife during the trials for his case. Their self-concepts before incarceration consists of self-descriptions that may fall under their self-image, looking-glass self and ideal self. They described various conforming characteristics and also non-conforming characteristics such as being an alcoholic, a womanizer and being rebellious. They have different perceptions of the deviant act as well, but all of them used mortification and victimage as a way to purify their guilt in different parts of their narrative. Inside the prison, all participants felt negatively at first, but after years spent in prison, they now have a positive outlook because of their feeling of spiritual awakening. The participants all have lost communication with their previous family origin, and marital family. The research found that the meaning of the concept of the family of the participants is shaped in such a way that it does not conflict with the present self-concept of the participant.
Thesis (B.A. in Speech Communication)--University of the Philippines Diliman
Includes bibliographical references and appendices.